Administration of antirheumatic drugs. Issue 2 (April 1976) - Wright, V; Hopkins, R
Abstract : A study of 200 rheumatic patients attending an outpatient clinic and 72 general practitioners (GPs) was undertaken in relation to the administration of antirheumatic drugs. (1) Both patients and GPs agreed that effectiveness, absence of toxicity, and once daily administration were the important features of administration. (2) Significant differences between GPs and patients were noted in that patients more frequently preferred capsules than tablets. (3) GPs thought red was the best colour for an antirheumatic tablet, whereas patients thought white, this opinion being partly determined by the possible confusion of red tablets with sweets by children. (4) In a survey of 174 outpatients with rheumatic diseases, those with rheumatoid arthritis did not like blister packaging. A detailed assessment of 30 patients with rheumatoid arthritis in hospital confirmed this. Patients with moderate or severe rheumatoid disease of the hands often could not extract tablets from blister packs. Those who could found the packs difficult to open, the tablets broke, and came out suddenly, falling to the floor.